Voltage stability index improvement system by optimal placement of STATCOM in distributed systems (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
To provide the needed load, an interlinked radial distribution network includes a high amountof nodes and branchings. In the context of Pakistan, increased electrical demand placesexcessive stress on the radial distribution network, affecting the overall network'sperformance and potentially leading to voltage collapse; hence, it is desirable to keep thevoltage at each bus within allowed limits. To tackle voltage stability indices concerns, severaltechnologies such as STATCOM and other downstream linked devices are used, howeverproper sizing and location is also a key obstacle in the network. This study provides a ParticleSwarm Optimization approach that finds the optimum position and configuration ofSTATCOM to be deployed on the real-time distributor by identifying the voltage regulationfor the lowest bus in the network. The installation of STATCOM in the right area increasedthe voltage stability index (VSI), effectively reduced energy loss, and boosted the voltagestability, according to the results.